Positive solutions for boundary value problem of sixth-order elastic beam equation - Zouaoui Bekri (Open Journal of Mathematical Sciences, 2020)
In this paper, we study the existence of positive solutions for boundary value problem of sixth-order elastic beam equation of the form \(-u^{(6)}(t)=q(t)f(t,u(t),u^{'}(t),u^{''}(t),u^{'''}(t),u^{(4)}(t),u^{(5)}(t)),~~0<t<1,\) with conditions \(u(0)=u^{'}(1)=u^{''}(0)=u^{'''}(1)=u^{(4)}(0)=u^{(5)}(1)=0,\) where \(f\in C([0,1]\times[0,\infty)\times[0,\infty)\times(-\infty,0]\times(-\infty,0]\times[0,\infty)\times[0,\infty)\rightarrow [0,\infty))\). The boundary conditions describe the deformation of an elastic beam simply supported at left and clamped at right by sliding clamps. We give sufficient conditions that allow us to obtain the existence of positive solution. The main tool used in the proof is the Leray-Schauder nonlinear alternative and Leray-Schauder fixed point theorem. As an application, we also give example to illustrate the results obtained.